Dis is Ability - Fraser, Jewel (Ars Medica, 2020)
Jon Williams, a 38-year-old artist with Down Syndrome, took up art after a nervous breakdown in 2015. His work has been well received and he has twice been the subject of a one-man exhibition at one of Trinidad and Tobago's most prestigious art galleries. His story is a testament to the value of parental love and reasonable expectations as regards self-discipline.